Peranan Kualitas Audit dalam Memoderasi Hubungan antara Kinerja ESG dan Nilai Perusahaan pada Perusahaan Energi di Indonesia - Siti Ambar Mukti Puji Lestari; J.B.Amiranto (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to examine and analyze the effect of ESG performance on firm value, with audit quality serving as a moderating variable. The sample of this research consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2025. Based on purposive sampling criteria, seven companies met the requirements for this study. The research utilizes secondary data obtained from the official IDX website, including annual reports and sustainability reports. The analytical tool employed to test the research hypotheses is EViews version 13. The findings indicate that ESG performance does not significantly affect firm value, and audit quality does not moderate the relationship between ESG performance and firm value